96 The beneficial impact of schwarz rounds for staff: 3 years' experience at a tertiary referral cancer centre. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - McNulty, M; Droney, J; Stevens, AM; Halley, A
Abstract : Background: Schwartz Rounds (SR) aim to provide a structured forum for staff to discuss the psychosocial and emotional issues of work in healthcare. Patient safety is linked with staff wellbeing, with potential associations between burnout and medical mistakes, and possible impact on effective organisational response to change. These issues are particularly relevant to the NHS and other healthcare systems currently. Aims: This service evaluation sought to explore the relevance and impact of SRs for healthcare staff. Methods: Retrospective analysis of feedback forms from staff who attended SRs from March 2015 to June 2018 at a tertiary referral cancer centre. Descriptive statistics were used to describe staff and their agreement with statements about their experience. Thematic analysis of free text comments was conducted. Results: 1091 feedback forms were analysed from 28 SRs with 3449 attendees (31.6% response rate). 963 (88%) agreed with the statement 'Today's Round will help me work better with my colleagues'. The main staff groups represented were: Nursing (36%), AHP's (29%) and administration (17%). Doctors represented 7%. 71% respondents disclosed if they had attended a SR before. Of those, 49% had been to between 1 and 5 SR, while 43.5% had never attended. 21% of respondents gave comments which were analysed for qualitative data. 81% positive, 3% negative, 4% neutral and 12% other comments were made. Keywords used by staff to describe the SR's emerged; insightful, reflection, interesting, inspiring, sharing, supportive. Poignant comments described relief from feelings of isolation and having been given 'the courage to keep going'. Conclusion: Our evaluation of 3 years' experience demonstrates that SRs are highly acceptable to staff who attend, as a means of interactive and supportive reflection. Qualitative data revealed that most staff described SRs in positive terms. Our evaluation supports evidence that SRs can be a source of support for staff.